Maria, Mariana na Serra do Ororubá - PE (1936-2016) - Aguiar Neto, Múcio Rodrigues Barbosa de (2016)
This thesis aims to investigate the phenomenon of the apparitions of Our Lady of Grace, the site Guard in Cimbres village in Pesqueira, Pernambuco, in the year 1936. In our first chapter we study the concepts of appearances and appearances occurred in Brazil; in the second chapter re-present the story of the apparitions of the Virgin of Grace, in the Serra do Ororubá; the third and final chapter study miracles, healings and graces in the eyes of the Church and popular. We recorded some alleged miracles occurred throughout history in Brazil, including those attributed to Our Lady of Grace, of Cimbres. Maria Mariana Serra do Ororubá is study of the apparitions phenomena from the perspective of religious studies.